2017
DOI: 10.1088/1361-6498/aa6732
|View full text |Cite
|
Sign up to set email alerts
|

Application of rodes software to experimental biokinetic data for dose assessment in mice and rats

Abstract: H Miloudi, M Locatelli, G Autret, D Balvay, A Desbrée, E Blanchardon, J M Bertho: application of RODES software to experimental biokinetic data for dose assessment in mice and rats. In support of experimental studies of chronic, long-term contamination in rodents, voxel-based computer models were built representing adult mice and juvenile, adult and elderly rats of both sexes. RODES software was created to calculate absorbed radiation doses to organs with these specific anatomical models. Absorbed doses were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Organ and tumor dosimetry calculations were performed using the Rodent Dose Evaluation Software (16,17). Briefly, pharmacokinetic data were input into a murine three-dimensional imaging-based dosimetry platform built on accurate MRI volumes to compute the intraorgan and interorgan and tumor-absorbed doses from alphaparticle, beta-particle, and gamma-emission transport.…”
Section: Translational Relevancementioning
confidence: 99%
“…Organ and tumor dosimetry calculations were performed using the Rodent Dose Evaluation Software (16,17). Briefly, pharmacokinetic data were input into a murine three-dimensional imaging-based dosimetry platform built on accurate MRI volumes to compute the intraorgan and interorgan and tumor-absorbed doses from alphaparticle, beta-particle, and gamma-emission transport.…”
Section: Translational Relevancementioning
confidence: 99%
“…To evaluate the additional absorbed radiation dose due to 137 Cs injection, we used the RODES software (Miloudi et al 2017 with the individual whole body measurements of 137 Cs during the experiment. The results (figure 5) showed that the range of the additional dose due to 137 Cs injection estimated in each individual animal was between 7.4 mGy and 9.3 mGy, without any significant difference according to the external irradiation group.…”
Section: Absorbed Radiation Doses Induced By 137 Csmentioning
confidence: 99%
“…Biodistribution studies were conducted to evaluate uptake and pharmacological distribution of fPSA (16,17). Briefly, pharmacokinetic data were input into a murine hu5A10 radioimmunotheranostics 3D imaging-based dosimetry platform built on accurate magnetic resonance imaging volumes in order to compute the intra-and inter-organ and tumor absorbed doses from alpha-particle, beta-particle and gamma-emission transport.…”
Section: Biodistribution and Dosimetry Studiesmentioning
confidence: 99%